Is there an indication to utilize intravenous iron in acute trauma patients? Why, how, and when. Issue 2 (April 2020) - Froessler, Bernd; Kurmis, Andrew; Papendorf, David
Abstract : Purpose of review: Traumatic injury has been described as a growing pandemic which has significant implications for global health. In the trauma setting, anemia is a common occurrence and is frequently inadequately addressed. It is associated with significant morbidity and incurs great cost – both to the patient and to the health system. The cause is multifactorial, and the pathophysiology is incompletely understood. Appropriate care of the trauma patient is a multidisciplinary responsibility and a focused approach to anemia is vital. The recommendation for restrictive transfusion strategies and the potential benefit of intravenous iron (IVI) in the perioperative setting, make the intervention an attractive proposition in the anemic trauma patient. Recent findings: In an era where the importance of patient blood management is recognized, there is significant attention being given to both the implications and the appropriate management of anemia, in various settings. Advances have been made in the understanding of the mechanisms underlying the anemia associated with traumatic injury and the efficacy of current interventions is being explored. This increased understanding of the pathophysiology behind the condition has also facilitated the postulation of potential therapeutic targets for the future. Summary: Suboptimally managed anemia impacts on clinical outcome and contributes to the burden of costs associated with trauma. The cause of the anemia associated with trauma is multifactorial and should be addressed at several levels. The role of IVI in this setting is yet to be clearly defined.